The Mortality Due to External Causes in Ukraine: Lives That Could Be Saved - Ryngach N. О. (Statistics of Ukraine, 2020)
The article’s objective is to assess the losses of human lives in Ukraine, resulting from the mortality due to external causes (by absolute number, rate and structure), reveal the patterns by gender and age, with distribution by main cause. A comparative analysis of the mortality due to external causes in Ukraine and other countries is made by data on the distribution of deaths by gender, age and cause of death, taken from the State Statistics Service of Ukraine, international and national databases. It is shown that the major share of deaths were due to four main causes accounted for more than 68% of all the cases: intentional self-harm (suicides); harm of undetermined intent; accidental poisonings caused by noxious substances; and transport accidents. An essential gender disproportion due to external causes is revealed: the mortality rate of males is 4.7 times higher than females. In Ukraine males account for 80.2% of the total deaths due to external causes (against two thirds, or 64.2%, in EU). The excess of males is the most significant in the causes such as drowning, suicides and accidental poisonings (with more than eight times to six times excess of the respective figure over females). In view of this, the share of deaths due to external causes in the overall structure of mortality was higher for Ukrainian males (8.4%) than for females (2.0%). The rate of sudden mortality (in the age younger than 65) due to external causes of death in Ukraine is 2.5 time higher than in Sweden chosen as a reference country, and thrice higher than in EU until 2004. The majority of deaths due to external causes in Ukraine are concentrated in this age group: nearly 80% in 2019 (against 49% in EU countries). A pressing social problem for modern Ukraine is the excessive mortality due to accidental poisoning and alcohol effects: from the age of 30 years and on, such cases exceed the poisonings caused by noxious substances (the gap being 1.75 times for the total population and more than trice (3.25 times) for the middle age of 45–49 years. Special attention is given to the problem of the increasing rate of deaths classified as “harm with undetermined intent” (which rate in Ukraine is seven times higher than in EU). It raises the need for analysis of the veracity of determined causes of death and quality enhancement of the official statistics for this class of causes in Ukraine, to have better understanding of the real situation and tendencies of change in the epidemiological situation with respect to external causes of mortality.